ANALISIS SEBARAN DAN PERKEMBANGAN INDUSTRI RUMAH TANGGA TENUN DI NAGARI HALABAN KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - Hidayah Dayah 06; Syafri Anwar (JURNAL BUANA, 2021)
This study aims to determine: (1) the distribution of the location of the weaving household industry in Nagari Halaban. (2) constraints on the weaving household industry in Nagari Halaban. (3) efforts to overcome obstacles in the weaving household industry in Nagari Halaban. This type of research is qualitative. The population in this study were weaving craftsmen in Nagari Halaban. Sampling by Quota sampling. With a total of 80 weaving craftsmen in Nagari Halaban. The research instruments used in this study were interviews, observations, and documentation. The results showed that: (1) The distribution of the woven household industry in Nagari Halaban is very strategic as a center for the development of the weaving industry. (2) Constraints for the weaving home industry, such as tools / raw materials, capital, industrial processes, labor, and marketing. The common obstacle experienced by craftsmen is capital. (3) These constraints do not hinder the development of the woven household industry in Nagari Halaban. Because, with tenacity the craftsmen have been able and able to find a way out of the obstacles they encounter.